The stoneflies (Insecta, Plecoptera) of the Talladega Mountain region, Alabama, USA: distribution, elevation, endemism, and rarity patterns - Scott Grubbs (Biodiversity Data Journal, 2018)
Background The Talladega Mountain region of eastern Alabama is the southernmost outlier of the ancient Appalachian Mountains, including the highest peaks and ranges in the state. Collections of stoneflies (Plecoptera) previously here have been sporadic yet has led to several new species descriptions in modern times (James 1974, James 1976, Stark and Szczytko 1976, Kondratieff and Kirchner 1996, Szczytko and Kondratieff 2015) and expanded our understanding of southeastern US stoneflies. During the period 2003–2012 we conducted an intensive inventory of the stonefly fauna of the Talladega Mountain region. We collected across all months from 192 unique localities, covering a broad range of stream sizes and elevation gradients present in the region. New information A total of 57 confirmed species across eight of the nine Nearctic families were collected as adults (Table 4), including four species described as new during the study period (Table 2). Leuctra crossi James, 1974 was easily the most common species collected. Median elevations per species ranged from 174 m (Clioperla clio (Newman, 1839)) to 410 m (Leuctra triloba Claassen, 1923 (Fig. 3). Dot distribution maps were included for all 57 species plus one for undetermined nymphs of Pteronarcys Newman, 1838 (Figs. 4–19). As many as seven species may be endemic to the region but sampling efforts northeastward into Georgia, plus additional focused sampling in Alabama and a comprehensive examination of all available material held in museums and personal collections, are needed for confirmation.